LEMBAGA PENGOLAHAN SAMPAH DALAM MENINGKATKAN KESADARAN LINGKUNGAN MASAYARAKAT DI KELURAHAN PEMATANG PUDU KECAMATAN MANDAU - Agustiadi '; Siti Sofro Siddiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted in Pematang Pudu Village with the aim of explaining how the role of the Garbage Bank is in increasing community environmental awareness and also explaining how the supporting and inhibiting factors of the Garbage Bank are in increasing community environmental awareness. This study uses a descriptive qualitative research method. Data collection was carried out using in-depth interview techniques, direct observation and documentation. The results of the analysis show that the role of the Garbage Bank is divided into four, namely the facilitative role, the educational role, the representative role, and the technical skill role. In carrying out its facilitative role, the waste bank provides free training to the community. In providing an educational role, the waste bank conducts outreach to homes and community institutions. In giving the role of waste bank representatives looking for partners to work together in obtaining profits. In carrying out the role of the garbage bank's technical skills in carrying out data collection and financial management. In this study there are several factors that support and hinder the waste bank in increasing environmental awareness. What supports it is the enthusiasm of the management of the waste bank, parties who help, as well as government support. The inhibiting factors are education, a low mindset, the selling price of waste is cheap compared to other collectors. Keywords: Garbage Bank, Role, Community